One Health in Switzerland: A visionary concept at a crossroads? (Swiss Medical Weekly, 2011)
One Health stands for the health of humans, animals and the environment. There is only one health in our entire ecosystem, and the equation for its promotion is in interdisciplinary cooperation. One Health benefits from synergies to generate added value and is a promising strategy to strengthen health systems. A growing number of One Health conferences worldwide bear witness to a spirit of optimism which should result in the implementation of a sustainable One Health policy globally, regionally, nationally and locally. The purpose of this study was to investigate the opportunities for implementation of the One Health concept in Switzerland. Between April and August 2010, semi-structured face-to-face interviews were conducted with 16 key experts selected from among the leading personalities in the Swiss health system. The experts confirmed the potential of the One Health concept for Switzerland. Barriers such as cultural differences, absence of evidence, federal structures and a relatively low degree of suffering were identified and a road map established, including research activities, capacity-building and a stakeholder approach to joint preparation and tailored implementation of the One Health concept in Switzerland. These data suggest that One Health can support the opinion leaders in their quest for solutions. The detailed and unbiased description of potential barriers and a clear guide for a step-by-step action plan represent suggestions for a realistic way forward. Experience gained and lessons learnt in Switzerland may be of interest to other countries and help communicate and promote the One Health concept.